The critter and other dogs. - Terhune, Albert Payson, 1872-1942. (New York, Grosset & Dunlap, 1961)
Seventeen short stories of heroic collie dogs.
Keywords: Collie -- Fiction; Dogs -- Fiction; Dogs -- Fiction; Short stories